Trends in the Use of Residential Settings Among Older Adults. (17th May 2021) - Toth, Matt; Palmer, Lauren; Bercaw, Lawren; Voltmer, Helena; Karon, Sarita L
Abstract: Objectives: As the U.S. population ages, the prevalence of disability and functional limitations, and demand for long-term services and supports (LTSS), will increase. This study identified the distribution of older adults across different residential settings, and how their health characteristics have changed over time. Methods: A cross-sectional analysis of older adults residing in traditional housing, community-based residential facilities (CBRFs), and nursing facilities using 3 data sources: the Medicare Current Beneficiary Survey (MCBS), 2008 and 2013; the Health and Retirement Study (HRS), 2008 and 2014; and the National Health and Aging Trends Study, 2011 and 2015. We calculated the age-standardized prevalence of older adults by setting, functional limitations, and comorbidities and tested for health characteristics changes relative to the baseline year (2002). Results: The proportion of older adults in traditional housing increased over time, relative to baseline ( p < .05), while the proportion of older adults in CBRFs was unchanged. The proportion of nursing facility residents declined from 2002 to 2013 in the MCBS ( p < .05). The prevalence of dementia and functional limitations among traditional housing residents increased, relative to the baseline year in the HRS and MCBS ( p < .05). Discussion: The proportion of older adults residing in traditional housing is increasing, while the nursing facility population is decreasing. This change may not be due to better health; rather, older adults may be relying on noninstitutional LTSS.